Workplace Diversity Training: Evoking Change or Reinforcing the Status Quo? - Patricia M. Thompson; Thomas V. Bettinger (Adult Education Research Conference, 2006)
In order to effectively support diversity initiatives in our institutions or to develop workplace diversity programs, we need to first define and deconstruct the issues which impede diversity initiatives. The purpose of this roundtable is to discuss how we define diversity; the role social identity plays in supporting and hindering workplace diversity initiatives; the impact of organizational culture or monoculturism on diversity initiative; and ways to address the issues of dominance which undergird organizations.
Keywords: Workplace diversity; HRD; multi-cultural education